Human geography : (McGraw-Hill, 2005)
A non-major introduction to human/cultural geography that focuses on culture, society, and human activity from a geographic perspective. The book is also designed for majors taking their first course in Human Geography. Fellmann provides a thorough, classic, up-to-date, and balanced approach to this broad range of topics. Among the most distinctive and important features of the text is its thorough and well-integrated coverage of gender roles in society and culture.Instructors and students using the sixth edition update will have access to PowerWeb, a course-specific website developed with the help of instructors teaching the course to provide instructors and students with curriculum-based materials, updated weekly assessments, informative and timely world news, refereed web links and much more